Об одном сюжете с ἐφ’ ἡμῖν и προαίρεσις в поздней античности [Grigorij I. Benevich. On ἐφ’ ἡμῖν and προαίρεσις in the Late Antiquity] - Беневич, Г. И. (Hyperboreus, 2011)
The paper deals with the distinction between natural will (θέλημα) and hypostatic choice (προαίρεσις), made by Maximus the Confessor in the Christological controversy and that made by Proclus between choice (προαίρεσις) and wish (βούλησις). It also touches upon Gregory of Nyssa’s use of προαίρεσις and Maximus’ understanding of ἐφ’ ἡμῖν.